ANALISIS KOTEKS PADA TANYA JAWAB PIDATO MENDIKBUD NADIEM MAKARIM DALAM SIMPOSIUM INTERNASIONAL - Maharani Yuanti, Ananda; Missriani, Missriani (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
The problem in this research is how to analyze the cotext in the question and answer session of Minister of Education and Culture Nadiem Makarim's speech at the International Symposium on Principals and School Supervisors. This study aims to determine the cotext (explanatory text) contained in each sentence of the question and answer session of Mendikbud Nadiem Makarim's speech at the international symposium of school principals and school supervisors. The data used in this study are secondary data taken from books, articles, and videos related to the purpose of the context analysis. This research uses descriptive qualitative research methods. The data collection technique used in the study was the observation technique. The validity of the data used source triangulation and the data analysis used was the content analysis technique. The results of this study are that there are several forms of cotext in the question and answer session of Mendikbud Nadiem Makarim's speech. For example, the first sentence is an opening greeting for Muslims who are always delivered / spoken before starting a conversation in formal and non-formal situations. The second sentence is a greeting addressed to the participants in the room. The greeting sentence can be "good morning, good afternoon, and good night" depending on the situation at the time of the event..